2022
DOI: 10.1021/acsaem.2c01559
|View full text |Cite
|
Sign up to set email alerts
|

Additive-Induced Film Morphology Evolution for Inverted Dion–Jacobson Quasi-Two-Dimensional Perovskite Solar Cells with Enhanced Performance

Abstract: In the past decade, three-dimensional (3D) perovskites have been under intense study. However, these devices always suffer from severe performance degradation. Recently, two-dimensional (2D) perovskites have attracted increasing attention due to their excellent environmental stability, but their low power conversion efficiency (PCE) limits their application. Therefore, many strategies have been applied to manipulate the crystallization and suppress the defects and low-n value phases. Additive engineering, as o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…As a result, out-of-plane oriented crystallization and ordered phase distribution are achieved. The thiourea (TU) [ 176 ] is positively utilized to make great efforts in optimizing the crystallization development, resulting in an increased grain size, flat and dense surface structure, and controlled delivery of n values for enhanced phase purity (Fig. 13 ).…”
Section: Dj-layered Halide Perovskites Materials and Devicesmentioning
confidence: 99%
“…As a result, out-of-plane oriented crystallization and ordered phase distribution are achieved. The thiourea (TU) [ 176 ] is positively utilized to make great efforts in optimizing the crystallization development, resulting in an increased grain size, flat and dense surface structure, and controlled delivery of n values for enhanced phase purity (Fig. 13 ).…”
Section: Dj-layered Halide Perovskites Materials and Devicesmentioning
confidence: 99%
“…Min et al also employed thiourea and MACl to synergistically facilitate the crystallization process, which resulted in a smooth and dense surface morphology, and improved phase purity. 130 Chen et al reported well-oriented PDA-based DJ perovskite films synthesized using FACl additive. 97 Fig.…”
Section: Functional Additives Additionmentioning
confidence: 99%
“…As an illustrative instance, in the context of planar n-i-p PSCs, the utilization of NiO@C nanoparticles as a highly effective interference layer, wherein their application successfully diminished the surface defects in the perovskite layer and facilitated improved charge transfer mechanisms . Recently, the additive engineering approach has proven to be an effective method in passivating surface defects or grain boundary defects of perovskite and facilitating homogeneous nucleation, thereby improving the stability of perovskite films. …”
Section: Introductionmentioning
confidence: 99%